Mark Proescholdt letter to James J. Dinsmore regarding a trip to northwest Iowa and bird sightings, June 26, 1987 - Proescholdt, Market al (1987)
Letter from Mark Proescholdt to James J. Dinsmore regarding a trip to northwest Iowa and bird sightings, June 26, 1987. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1987. Epson - sheet feed/flatbed